Pengaruh Independensi, Keahlian Profesional Dan Dukungan Manajemen Terhadap Efektivitas Fungsi Audit Internal - Afdel Hamdi; Vita Fitria Sari (Universitas Negeri Padang, 2019)
Internal audit is the important things in govermant organizationl structures, when the function of internal audit by good configuration, so the internal audit can be important actor in govermant process and institute accountability of sector public. So that, needed talk about the influence factor of efectifity internal audit by independent, profesionality and manajeme support. The purpose of this research is to knowing about the influence of independent, profesionaliti and manajemen support to word internal auditor in govermant in inspectorat sumatera barat province. The result of this research show that independent, profesionality, and manajemen support have possitve influence to word the function of efectifity internal audit in sumatera barat inspectorat